Modeling and Computation of Nano-Optics (CSIAM Transactions on Applied Mathematics, 2020)
This work is devoted to a review of our recent studies in the modeling andcomputation of nano optical devices. Motivated by technological advances at nanoscale, to quantitatively understand the mechanism and improve the designing, wemake an effort to model nano optical systems involving multiple physical processesacross different time and space scales, and develop multiscale and adaptive numericalmethods for simulation. Challenges on rigorous analysis of the models and algorithmsare also discussed.